2016
DOI: 10.5897/ajmr2016.8143
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid bacteria from traditionally processed corn beer and palm wine against selected food-borne pathogens isolated in south west region of Cameroon

Abstract: The present study was undertaken to assess the inhibitory potential of lactic acid bacteria isolated from traditionally processed corn-beer and palm-wine on Escherichia coli, Salmonella typhi and Staphylococcus aureus. Lactic acid bacteria were isolated on MRS agar using pour plate method. The catalase negative and Gram positive isolates were selected as presumptive lactic acid bacteria and were biochemically characterized using the API 50 CHL BioMerieux kit to identify them at species level. The LAB isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
2
1
0
1
Order By: Relevance
“…From our study, probiotic bacterium lactobacillus fermentum strain BB101 (F1) and Lactobacillus casei strain 02 (F2) had a good acid and bile tolerance capacity. These results of acid and bile salt tolerance is similar to that obtained by other authors who reported that Lactobacilli which were isolated from milk products and palm wine showed resistance to low and high pH respectively [26] [27]. Safety is also a significant consideration while selecting potential probiotics before they are available for public usage, these strains were gamma haemolytic (no haemolysis) and sensitive to all antibiotics tested, these results is similar to previous studies [26] [27].…”
Section: Discussionsupporting
confidence: 91%
“…From our study, probiotic bacterium lactobacillus fermentum strain BB101 (F1) and Lactobacillus casei strain 02 (F2) had a good acid and bile tolerance capacity. These results of acid and bile salt tolerance is similar to that obtained by other authors who reported that Lactobacilli which were isolated from milk products and palm wine showed resistance to low and high pH respectively [26] [27]. Safety is also a significant consideration while selecting potential probiotics before they are available for public usage, these strains were gamma haemolytic (no haemolysis) and sensitive to all antibiotics tested, these results is similar to previous studies [26] [27].…”
Section: Discussionsupporting
confidence: 91%
“…This phenomenon implies their potential applicability in counteracting diverse foodborne pathogens, thereby reaffirming their role in enhancing food safety measures. This observation aligns with the conclusions drawn by Fossi et al (2016), who extensively explored the potential of LAB bacteriocins in the context of food preservation.…”
Section: Discussionsupporting
confidence: 90%
“…Locally harvested palm wine and traditionally processed corn beer have been exploited as suitable sources for screening various LAB [23]. In Cameroon, palm wine and corn beer are widely consumed with little or no knowledge of the presence of a predominant LAB population [13].…”
Section: Discussionmentioning
confidence: 99%